Learning Management Based on Iqra Method And Drill Method For Students With Disabilities - Utami, Mulya; Asrori, Achmad; Anwar, Chairul (Journal of Advanced Islamic Educational Management, 2022)
This study aims to describe and analyze the planning, process, and evaluation of learning using the iqro' method, complemented by the drill method, in improving the ability to read hijaiyyah letters of students with disabilities. The subject of this research is the teacher of Islamic learning. This research uses a qualitative approach and a descriptive research type. The data collection techniques used were observation, interview, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of this study are as follows: Learning plans made by Islamic Religious Education teachers at SLB Muhammadiyah Gamping are not part of the established curriculum and are not specifically written about learning to read hijaiyyah letters using the iqro' method equipped with the drill method. the learning process of reading hijaiyyah letters The method used is the iqro' method equipped with the drill method, the material given refers to the iqro' guidebook according to the ability of the students, and the learning media used are videos and hijaiyyah letter cards. The evaluation used in learning to read hijaiyyah letters using the iqro' method equipped with the drill method is oral and written. The learning outcomes of students with disabilities in the form of the ability to read hijaiyyah letters consist of students who have not maximized their potential to reach half of the target percentage that has been set, and student learning outcomes in one semester are written in the student learning outcomes report or report card